THE CONCEPT OF MONEY IN ENGLISH AND UZBEK LANGUAGE - Nozima Niyazova Ilhom qizi (Web of Journals Publishing, 2026)
This article explores the concept of money from a linguistic and cultural perspective, focusing on its representation in the English and Uzbek languages. The study analyzes how money is conceptualized, lexicalized, and metaphorically expressed in both languages. By comparing semantic fields, phraseological units, and cultural connotations associated with money, the article reveals similarities and differences shaped by historical, economic, and sociocultural factors. The research contributes to contrastive linguistics and intercultural communication by highlighting how language reflects societal attitudes toward economic values.
Keywords: Money, concept, linguistic worldview, English language, Uzbek language, metaphor, semantics, culture.